"Fast tracking" patients with a proximal femoral fracture. Issue 2 (March 1996) - Ryan, J; Ghani, M; Staniforth, P; Bryant, G; Edwards, S
Abstract : OBJECTIVE--To assess the management of elderly patients presenting to the accident and emergency (A&E) department with a proximal femoral fracture. METHODS--A retrospective audit carried out on 30 patients with proximal femoral fracture showed an unacceptably long waiting time in the A&E department. A new "fast track" system for managing these patients, involving the use of a flow chart for expediting admission, was devised. A prospective study of 100 patients > 60 years of age with proximal femoral fracture admitted by fast track system was then carried out. RESULTS--Implementation of the fast track system resulted in earlier admission to the ward (median time to admission 2.5 h v 4.5 h in the retrospective audit, P < 0.001). Eighteen patients were not admitted by fast track during the study period, in some cases because of inconclusive diagnosis or because there was no identifiable orthopaedic bed; mean admission time for this group was 4 h 8 min. CONCLUSIONS--The fast track system was of benefit to all involved, including the patient, A&E staff, ward staff, and orthopaedic personnel.